Perempuan dan Banten Pergulatan Status di Tengah Abrasi Simbolisme Keagamaan Pada Masyarakat Bali - I Made Ariyasa Giri; Ni Nyoman Lisna Handayani; I Putu Suardipa (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2020)
The specific objective of this research is to develop a model of the inheritance of a national spirit among generations of women, especially among the people in Buleleng Regency in an effort to transform religious values ​​and share responsibility for the implementation and development of religion. This research will be conducted in Buleleng Regency. The research sample consisted of: Balinese women. The research instrument used: observation sheets, interview guidelines, questionnaires, documentary studies. This research is a development research that combines the Borg and Gall model with the Miles and Huberman model. All research data will be analyzed using cross-site analysis techniques, detailed descriptions, explanation of participatory appraisal (EPA), and SMART. This research will be conducted for 1 year (2020), in which the resulting products are as follows: (1) a profile of religious insights and values, (2) a model of empowering the role of women and offerings in an effort to transform religious values ​​and share responsibility for religious implementation and development. valid, practical, and ready to use, (3) scientific articles, and (4) research reports.